Seasonal Variations in Zooplankton Diversity and Water Quality Across Selected Freshwater Lakes in Northern India - Seema; Anil Kumar; Suresh Kumar; Nitesh Singh (The Bioscan, 2025)
Aquatic ecosystems, which include a wide variety of habitats such as lakes, rivers, ponds, and estuaries, are among the most intricate and ecologically varied environments on Earth. However, both natural seasonal changes and man-made stressors like pollution and habitat modification are posing a growing danger to these ecosystems. The seasonal diversity and distribution of zooplankton species in three freshwater lakes in northern India—Tilyaar Lake (Rohtak), Karna Lake (Karnal), and Tikkar Taal (Panchkula)—are thoroughly examined in this research. Four primary taxonomic groups—Copepoda (18 species), Rotifera (31 species), Cladocera (18 species), and Ostracoda (6 species)—accounted for the 73 zooplankton species that were discovered. The zooplankton diversity was highest during the pre-monsoon season and lowest during the monsoon season, most likely as a result of surface runoff and rainfall dilution effects. The species diversity was highest in Tilyaar Lake and lowest in Tikkar Taal, with Copepods predominating in Rohtak, Rotifers and Ostracods peaking in Karnal, and Cladocera being most prevalent in Panchkula. Total Dissolved Solids (TDS), Nitrate, Sulfate, Turbidity, and Biological Oxygen Demand (BOD) were among the physico-chemical parameters that showed substantial seasonal fluctuation in water quality analysis, with the majority of these parameters peaking during the Post-Monsoon season. The relationship between BOD levels and zooplankton abundance is inverse, indicating that a larger organic load during the winter months promotes more biological activity, which in turn affects community structure. The study emphasizes how crucial zooplankton are as bioindicators for evaluating aquatic health because of how sensitively their variety and density react to human inputs like sewage discharge and environmental changes. For the ecological monitoring and management of freshwater resources under the stresses of urbanization and climatic fluctuation, the study provides important baseline data on species composition, seasonal population dynamics, and water quality variations.